Pontas e velocidade de deslocamento na deposição de gotas da pulverização na cultura do algodão - Cavalieri, Jhonatan Diego [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Dois experimentos foram conduzidos em lavoura comercial de algodão, Gossypium hirsutum L., na safra agrícola 2012/2013, em estádios de desenvolvimento distintos (B9 e F13), para avaliar o efeito de pontas de pulverização de energia hidráulica e um sistema de pulverização de energia centrífuga sob diferentes velocidades de deslocamento do pulverizador sobre o depósito, cobertura e espectro de gotas da pulverização. O delineamento experimental foi o modelo de blocos casualizados, com doze tratamentos e quatro repetições. Os tratamentos foram distribuídos em arranjo fatorial 3 x 4 (três técnicas de pulverização, sendo duas delas de energia hidráulica: jato plano simples; jato plano simples inclinado com indução de ar, sob taxa de aplicação de 120 L.ha-1; e sistema de energia centrífuga - atomizador rotativo de disco - sob taxa de aplicação de 20 L.ha-1, combinadas a quatro velocidades de deslocamento: 12, 15, 18 e 25 km.h-1). Para a avaliação do depósito da pulverização, alvos artificiais foram fixados na superfície adaxial e abaxial das folhas do ápice e base do algodoeiro (Estádio B9) e também na parte média das plantas (Estádio F13). Após a pulverização de um marcador cúprico (oxicloreto de cobre), os alvos foram coletados, imersos em solução extratora de ácido nítrico a 1,0 mol.L-1, procedendo-se a leitura da solução por espectrofotometria de absorção atômica. Para a análise da cobertura e espectro de gotas da pulverização...

Two experiments were conducted in commercial cotton farming, Gossypium hirsutum L., in the 2012/2013 season, in different growth stages (B9 and F13), to assess the effect of centrifugal energy system and hydraulic energy spray nozzles under different displacement speeds of the sprayer on deposit levels, coverage and spray droplets spectrum. The experimental design was randomized blocks, with twelve treatments and four replications. The treatments were arranged in a factorial scheme 3 x 4 (three spray nozzles: standard flat-fan, flat-fan tilted with air-induction under application rates of 120 L.ha-1, and centrifugal energy system - rotating disc atomizer - under application rates of 20 L.ha-1, combined with four displacement speeds: 12, 15, 18 and 25 km.h-1). To evaluation of spray deposit, artificial targets were fixed in upper side and underside of leafs on apex and base of cotton plants (growth stages B9), and also in the middle part of the plant (growth stages F13). After spraying of a cupric tracer (copper oxychloride), targets were collected and placed in nitric acid extractor solution at 1.0 mol L-1. The tracer quantification was made by atomic absorption spectrophotometry. To analysis of spray coverage and droplet spectrum, water sensitive paper were fixed on stakes at the height upper, middle and lower parts of the plant. After spraying, the targets were removed, scanned and analyzed by DepositScan software. The droplet spectrum with centrifugal energy system was more homogeneous, with greater penetration of the droplets and uniformity of spray deposition on the canopy in both growth stages of crop. The increase... (Complete abstract click electronic access below)
Keywords: Defensivos vegetais - Tecnologia de aplicação; Pulverização; Algodão - Cultivo; Defensivos agrícolas; Cotton